Stress, Ineffective Coping, and Anxiety in Productive-Age Diabetes Mellitus Patients: Implications for Mental Health Diagnosis - Cecilia Indri Kurniasari; Margaretha Kurniastuti; Fittriya Kristanti (FORIKES, 2026)
Diabetes mellitus cases increased significantly in the 15-54 age group, according to doctors' diagnoses. Diabetes Mellitus in this age range causes a variety of risk factors that might lead to early symptoms of mental health disorders, such as irritability, anxiety, fatigue, and fear. The presence of early symptoms of mental health disorders can have a negative impact on the quality of life of productive-age people with Diabetes Mellitus, including decreased concentration and work productivity, a considerable deterioration in body function, and a drop in social functioning. This study aimed to explore and understand in-depth experiences of mental health disorders in the productive age group with Diabetes Mellitus. This study employed a phenomenological approach. Six participants (two men and four women) who had been diagnosed with Diabetes Mellitus by a doctor served as informants for the research. Data was collected through in-depth interviews, observations, and questionnaires. Data analysis was performed using thematic analysis with NVivo 12 software. The findings of this study reveal major mental health issues in the form of psychological symptoms (stress and anxiety) during Diabetes Mellitus diagnosis and treatment. In conclusion, people with diabetes mellitus in the productive age group exhibit significant symptoms of mental health issues such as stress, ineffective coping, and anxiety, which means that a diagnosis is required to ensure appropriate mental health interventions.Keywords: productive age group; mental health issues; diabetes mellitus